Analysis of diabetic nephropathy in type 2 diabetes mellitus and prediabetes - T. A. Garkusha; E. S. Stolyarevich; V. A. Khorzhevskiy; S. V. Ivliev; M. A. Firsov; А. Yu. Terskikh (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Background. Malignant neoplasms are widespread, and the ambiguous relationship between them and hyperglycemia emphasizes the importance of studying them. On the one hand, diabetes mellitus and prediabetes increase the risk of developing malignant tumors. On the other hand, malignant tumors and drugs intended for their treatment can lead to hyperglycemia. Regardless of the origin, diabetes mellitus and prediabetes may develop diabetic nephropathy. Aim of study: to analyze the functional state of the kidneys in patients with diabetes mellitus and prediabetes with kidney neoplasms.Object and methods. There was a study of 141 patients with a kidney tumor who underwent nephrectomy. For histological examination, a fragment of the kidney parenchyma was taken at a distance of at least 4 cm from the tumor. Histochemical stains, immunofluorescence reaction and electron microscopy were performed. Assessment of laboratory parameters was carried out before the surgical treatment, 3 days, 3 months, six months and a year after the operation. Parameters such as the level of protein in the urine, the presence and number of altered erythrocytes in the urine, and the glomerular filtration rate were assessed using the CKD-EPI formula.Result. Diabetic nephropathy was detected in 44 patients (31.2%). Diabetes mellitus was previously diagnosed in 10 patients (22.7%), prediabetes was diagnosed in 34 patients (77.3%). After nephrectomy, patients with prediabetes and type 2 diabetes mellitus showed a sharp decrease in glomerular filtration rate (GFR). In the subsequent period, in patients with type 2 diabetes, there is a stable decrease in GFR. In patients with prediabetes, hyperfiltration is observed within six months, however, a year after the operation, GFR decreases again.Conclusion. Widespread diabetic nephropathy in patients, it is advisable to jointly manage patients with an oncologist, nephrologist, endocrinologist, clinical pharmacologist.